Study on audiometer calibration at the extended high-frequency range 8–16 kHz. (January 2022) - El-Basheer, Tarek M.
Audiometry is a branch of acoustical measurements that concentrated on testing the devices related to hearing and used in medical part such as audiometer. It is substantial to calibrate the audiometer to assure the measurement traceability and to safe human health. So, it is considered as a major claim. The importance of calibration comes from the request for advanced instrument to test accurately the hearing loss for human, especially for those people who might be at risk due to noise. The conventional audiometry covered from 125 to 8 kHz, while the extended high-frequency (EHF) audiometry above 8 up to 20 kHz, the last-mentioned type may be useful in early diagnosis of hearing loss. The audiometer calibration performed using ear simulator, standard or working microphone, sound level meter, and frequency analyzer according to IEC60645-1. The physical parameters such as sound pressure level, frequency and distortion may be affected by environmental conditions such as temperature change. The gained results observed that the measured value of all the tests performed was affected by temperature variation. There were deviations observed from each performed test's nominal values in the calibration process as the temperature varies from 16 to 40°C. So, this is a detailed study for the significance, method, and uncertainty estimation for audiometer calibration covering the EHF ranges within the temperature from 16 to 40°C.